Direct aerobic oxidation (DAO) of chlorinated aliphatic hydrocarbons: A review of key DAO bacteria, biometabolic pathways and in-situ bioremediation potential. (April 2022) - Xing, Zhilin; Su, Xia; Zhang, Xiaoping; Zhang, Lijie; Zhao, Tiantao
Graphical abstract: Highlights: Methylobacterium and Proteobacterium genera were the most common DAO bacteria. Trans-1, 2-dichloroethylene and 1, 2-dichloroethane are readily biodegradable. Direct aerobic oxidation of chlorinated aliphatic hydrocarbons is a general process. Sufficient oxygen supply is necessary for CAH removal in reactors and fields. Abstract: Contamination of aquifers and vadose zones with chlorinated aliphatic hydrocarbons (CAH) is a world-wide issue. Unlike other reactions, direct aerobic oxidation (DAO) of CAHs does not require growth substrates and avoids the generation of toxic by-products. Here, we critically review the current understanding of chlorinated aliphatic hydrocarbons-DAO and its application in bioreactors and at the field scale. According to reports on chlorinated aliphatic hydrocarbons-DAO bacteria, isolates mainly consisted of Methylobacterium and Proteobacterium . Chlorinated aliphatic hydrocarbons-DAO bacteria are characterized by tolerance to a high concentration of CAHs and highly efficient removal of CAHs. Trans-1, 2-dichloroethylene (t-DCE) is easily transformed biomass for bacteria, followed by 1, 2-dichloroethane (1, 2-DCA), dichloromethane (DCM), vinyl chloride (VC) and cis-1, 2-dichloroethylene (c-DCE). Significant differences in the maximum specific growth rates were observed with different CAHs and biometabolic pathways for DCM, 1, 2-DCA, VC and c-DCE degradation have been successfully parsed. Detection of the functional genes etnC and etnE is useful for the determination of active VC DAO bacteria. Additionally, DAO bacteria have been successfully applied to CAHs in new types of bioreactors with satisfactory results. To the best of the authors' knowledge, only one study on DAO-CAHs was conducted in-situ and resulted in 99% CAH removal. Lastly, we put forward future development prospect of chlorinated aliphatic hydrocarbons-DAO.